The impact of different equine influenza vaccine products and other factors on equine influenza antibody levels in Thoroughbred racehorses. (24th November 2014) - Ryan, M.; Gildea, S.; Walsh, C.; Cullinane, A.
Summary Reasons for performing study More knowledge of equine influenza (EI) vaccine usage in training yards and the factors that influence serological response to vaccination are required to determine evidence‐based vaccination strategies. Objectives The aim of this study was to ascertain the vaccination history of a population of Thoroughbred racehorses and identify factors that impacted on their antibody titres against EI. Study design Observational field study. Methods The study population consisted of 102 vaccinated Thoroughbred horses in training on a single premises. The vaccination histories recorded in their official passports were analysed. Blood samples for serological testing were collected by the veterinary surgeon one month after booster vaccination with ProteqFlu‐Te. Antibodies against EI were measured by single radial haemolysis (SRH). Multivariate statistical analysis was undertaken to determine the predictors of SRH antibody titres. Results There was a strong correlation between age and number of vaccine doses received. Over 70% of horses received their first vaccine dose between ages 6 and 12 months. On average, horses had received 6 vaccine doses and the mean interval between booster vaccinations was 7.7 months. The majority of horses (95%) received more than one influenza vaccine product while 32% had received 3 vaccine products. Significantly higher antibody levels were observed in females than males and there was a significant association between the number of vaccine products administered and antibody levels. In contrast, a negative association between number of vaccine doses and SRH antibody level was demonstrated. Conclusions Important predictors of EI antibody titres in racehorses were sex, number of vaccine doses received and number of different vaccine products administered.